2010
DOI: 10.1007/s12053-010-9078-2
|View full text |Cite
|
Sign up to set email alerts
|

Energy efficiency development in German and Colombian non-energy-intensive sectors: a non-parametric analysis

Abstract: This paper measures energy efficiency development in non-energy-intensive sectors (NEISs) in Germany and Colombia from a production-based theoretical framework using Data Envelopment Analysis (DEA). Using data from the German and Colombian Annual Surveys of Industries from 1998 to 2005, the analysis compares energy efficiency performances in German and Colombian NEISs at two levels of aggregation and then applies several alternative models. The results show considerable variation in energy efficiency perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(21 citation statements)
references
References 39 publications
2
19
0
Order By: Relevance
“…al. (2011), Mekaroonreung & Johnson (2009 and Ines and Martinez (2011) to measure the TE in the energy industry. The sample of the refineries studied consists of 12 refineries under the direction of NRC, MRC and SRC.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…al. (2011), Mekaroonreung & Johnson (2009 and Ines and Martinez (2011) to measure the TE in the energy industry. The sample of the refineries studied consists of 12 refineries under the direction of NRC, MRC and SRC.…”
Section: Methodsmentioning
confidence: 99%
“…The author proposed some measures that could be applied by the government to stimulate the efficiency of the housing sector in Iran. Ines and Martinez (2011) used the DEA to measure energy efficiency development in the non-energy-intensive sectors (NEISs) in Germany and Colombia through a production-bases theoretical framework using data from 1998-2005. The authors compared energy efficiency performances at two levels of aggregation and then applied different alternative models.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Gross production value (y d ) represents actual economic results at the field level. Previous studies have considered the gross production value (y g ) as the industrial output (e.g., [54][55][56][57]). This paper uses the outputs of gross production value (y d ) and the three workplace injury rates (being wounded or ill (y u 1 ), disability (y u 2 ), and death (y u 3 )).…”
Section: Data Sources and Variablesmentioning
confidence: 99%
“…The study period is 1997-2014 because Chongqing became a municipality in 1996. Based on economic growth theory, previous studies have indicated that the performance evaluation focus on physical capital stock, human capital stock, and output value [54][55][56]. Warr and Ayres [57] implicated energy and environmental policy that differ significantly from the traditional growth theory.…”
Section: Datamentioning
confidence: 99%